ANALISIS FINANCIAL DISTRESS MENGGUNAKAN METODE ALTMAN Z-SCORE DAN ZMIJEWSKI PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Rahmawati, Suci; Santoso, Budi (Jurnal Nusa Akuntansi, 2025)
This study aims to analyze Financial distress in companies in the Property and Real Estate sectors using the Altman Z-Score model and the Zmijewski model. This study also aims to find out the comparison between the Altman Z-Score model and the Zmijewski model in predicting bankruptcy, as well as to find out the level of accuracy in the Altman Z-Score model and the Zmijewski model. This study uses descriptive analysis, which is an analysis by describing or describing the data that has been collected, while this research approach is quantitative because the research data is in the form of numbers, data analysis techniques in financial statements. Based on the results of the calculation research using the Altman Z-Score model and the Zmijewski model , there is a difference in the results of the analysis because the value of financial ratios gives different assessments to Property and Real Estate companies. The Zmijewski model has a higher accuracy rate compared to the Altman Z-Score method which has a lower level of accuracy in predicting the Financial distress pads of companies in the Poperty and Real Estate sectors listed on the Indonesia Stock Exchange in the 2019-2023 period.